Diagnosis of portal vein tumor thrombosis in colorectal carcinoma in fluorodeoxyglucose positron emission tomography—computed tomography scan and its clinical implication - Shah, Digish (World Journal of Nuclear Medicine, 2020)
Hypercoagulable state is seldom associated with colorectal carcinoma either in the form of bland thrombosis or tumor thrombosis (TT). Venous TT should not be overlooked while deciding treatment of colorectal cancer due to its propensity to complicate the disease in terms of morbidity and mortality even in favorable prognostic case of colorectal cancer. Fluorodeoxyglucose positron emission tomography—contrast-enhanced computed tomography (FDG PET-CECT) scan has proven its role in staging of colorectal cancer and also to diagnose tumor venous thrombosis. Here, we are presenting a case of a 61-year-old male patient having adenocarcinoma of rectosigmoid colon, and on pretherapy FDG PET-CECT scan, he was found with portal vein TT and its related complication which is helpful for staging, treatment planning, and prognostication.
Keywords: Colorectal carcinoma; fluorodeoxyglucose positron emission tomography—contrast-enhanced computed tomography; portal venous tumor thrombosis